Kuratorial Solo International Performing Arts (SIPA) 2021 sebagai Bentuk Inovasi dan Konsistensi Festival Berskala International - I Wayan Dana; Rika Amalia Putri (Dance and Theatre Review, 2022)
Solo International Performing Arts (SIPA) 2021 Curatorial as a Form of Innovation and Consistency on an International Scale Festival This research focuses on the curatorial process in Performing Arts practice by taking a case study at the largest annual Performing Arts event in the city of Solo, SIPA (Solo International Performing Arts) in 2021. SIPA Festival has a curatorial concept that is detailed and mature and relevant to the circumstances of the times. Curatorial at the SIPA Festival focuses on the selection of event themes, mascots, and the selection of performers. The research method used is a qualitative method, which will focus on observation, documentation, and structured interviews. The main source of data is from the description of the source, and the memory of the source. The results of this study are about the explanation of the curatorial process in the series of SIPA 2021 events,- and the identification of the concept of curatorial thinking. Each SIPA 2021 performer has their own reasons why they were chosen to perform on the magnificent stage of SIPA 2021, this reason is in the description of the curators. The standards applied by SIPA Festival for its performers are absolute requirements that must be met by performers in order to be able to display their works on the SIPA 2021 stage.Keywords: Solo International Performing Arts, Festival, Performance Art, Curatorship, Curator